Calcium homeostasis in trypanosomatids: A review of molecular targets and inhibitors - Coelho, Natália Caroline Costa [UNESP]; Velásquez, Angela Maria Arenas [UNESP]; de Lima, Jhonatan Santos [UNESP]; Ramos, Ana Laura Dias [UNESP]; Cilli, Eduardo Maffud [UNESP]; Graminha, Marcia A S [UNESP] (Elsevier, 2025)
Calcium ion (Ca²⁺) signaling plays a pivotal role in the survival, differentiation, and virulence of trypanosomatids, including Leishmania spp., Trypanosoma brucei, and Trypanosoma cruzi, making it an attractive therapeutic target. This review integrates current knowledge on Ca²⁺ homeostasis in these parasites, addressing the plasma membrane, endoplasmic reticulum (ER), acidocalcisomes, mitochondria, lysosomes, and other organelles, with particular emphasis on key transporters and signaling pathways. In addition, we summarize genetic and pharmacological strategies used to validate Ca²⁺-related targets and highlight recent advances in both repurposed and novel compounds that disrupt Ca²⁺ homeostasis in trypanosomatids.